If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(x + 3) = 648 Reorder the terms: x(3 + x) = 648 (3 * x + x * x) = 648 (3x + x2) = 648 Solving 3x + x2 = 648 Solving for variable 'x'. Reorder the terms: -648 + 3x + x2 = 648 + -648 Combine like terms: 648 + -648 = 0 -648 + 3x + x2 = 0 Factor a trinomial. (-27 + -1x)(24 + -1x) = 0Subproblem 1
Set the factor '(-27 + -1x)' equal to zero and attempt to solve: Simplifying -27 + -1x = 0 Solving -27 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '27' to each side of the equation. -27 + 27 + -1x = 0 + 27 Combine like terms: -27 + 27 = 0 0 + -1x = 0 + 27 -1x = 0 + 27 Combine like terms: 0 + 27 = 27 -1x = 27 Divide each side by '-1'. x = -27 Simplifying x = -27Subproblem 2
Set the factor '(24 + -1x)' equal to zero and attempt to solve: Simplifying 24 + -1x = 0 Solving 24 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -24 + -1x = 0 + -24 Combine like terms: 24 + -24 = 0 0 + -1x = 0 + -24 -1x = 0 + -24 Combine like terms: 0 + -24 = -24 -1x = -24 Divide each side by '-1'. x = 24 Simplifying x = 24Solution
x = {-27, 24}
| 3x^2/5=6 | | 9.65s=308.80 | | X^2-154x+4=1000 | | 4x+7-30=27 | | 5(2y-1)=29 | | 13x-4(5x-8)+7=0 | | 2a^2-200=a^2+200 | | 2z=6.6 | | -x+4=-3x-2 | | 5x^2-3=3x+12 | | z+17=34 | | 2.2z^2=131 | | P(x)=x^3+x^2-10x-10 | | 1=49-3y^2 | | (x-8)(8x-1)=0 | | -13x^2=4212 | | 17y=340 | | 18x=306 | | y=8*-8 | | 12(k-4)+(5(k+3)(k-4))=-24(k+3) | | 5y+6=25y-106 | | 4*2-3y=17 | | 40x+20(1.5x)=3420 | | y=8*7 | | 3/4m-=16 | | -13p^2=4212 | | y=8*6 | | 3(x-7)=-30 | | 6x+5y=-17 | | 8x+4=9x-2 | | (2v-4)(v^2-3v-4)=0 | | (2x+15)+45=180 |